Evaluating the Association of Keratocunus with Consanguinity - Sohaib Afzal, Mohammad Aamir Khan, Shahid Anwar Bhatti, Muhammad Imran Ali, Aftab Ahmed Khan, Muhammad Awais Ashraf (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Purpose of this study is to determine the frequency of keratoconus with consanguinity. Study Design: Comparative/cross-sectional study Place and Duration: This comparative/cross-sectional study was conducted at Shahida Islam Medical and Dental College Lodhran and Jinnah International Hospital, Abbottabad in the period from May, 2022 to October, 2022. Methods: Total 53 patients of keratoconus were presented in this study. Included patients were aged between 8-32 years. Participants completed a self-administered survey that inquired about demographic information, KC findings, clinical symptoms, and parental marital status. All data was analyzed using SPSS 20.0. Results: There were 31 (58.5%) females and 22 (41.5%) males in all cases. Mean age of the patients was 19.25±12.92 years. 35 (66.03%) cases had rural residency and 18 (33.97%) cases were had urban residency. 25 (47.2%) cases had poor socio-economic status. Of the patients surveyed, 29 (54.7%) had first-cousin weddings between their parents, 16 (30.2%) had second-cousin marriages, 5 (9.4%) had third-cousin marriages, and 3 (5.7%) had marriages beyond the immediate family. Significant associations between consanguinity and KC were found at the p <0.05 level. Patients with first-degree consanguineous parents were shown to be more likely to have keratoconus and to have more advanced cases of the disease. Conclusion: Results from this study provide credence to the idea that there is still a significant direct correlation between KC and consanguinity. According to the findings, first-degree parental consanguinity poses a much greater risk of KC development than other types of intermarriage. The progression of KC was shown to be faster in this vulnerable population. Keywords: Consanguinity, Inheritance,Genetics, Keratoconus